LIGHTWEIGHT OPTIMIZATION DESIGN OF BODY-IN-WHITE BASED ON NSGA-II MIXED SENSITIVITY ANALYSIS - ZHAO ShuEn; YANG MingSen; PENG GuangXu (Jixie qiangdu)
With the problem of lightweight for body-in-white, a parametric optimization method based on mixed sensitivity analysis was proposed. The bending stiffness and modal properties of body-in-white were calibrated through the finite element simulation. Then the model was used to do mixed sensitivity analysis about stiffness and modal by experiment design, and related parts that have little influence on stiffness and modal properties were screened out. Takes thickness of related parts as design variables, the body-in-white quality and bending and torsion stiffness as the optimization targets, modal properties as constraint. The body-in-white lightweight of multi-objective optimization design was carried out by NSGA-II. Then simulate calculation was carried out by Isight to optimize the thickness of those parts, so as to realize the lightweight optimization design of the body-in-white structure. The simulation results show that its stiffness and modal performance were guaranteed after the parametric optimization, and the weight of the body-in-white was reduced by 5.7% of the original structure.